Influence of native ureolytic microbial community on biocementation potential of Sporosarcina pasteurii - Murugan, Raja; Suraishkumar, G.K.; Mukherjee, Abhijit; Dhami, Navdeep (NATURE PORTFOLIO, 2021)
Microbially induced calcium carbonate precipitation (MICP)/Biocementation has emerged as a promising technique for soil engineering applications. There are chiefly two methods by which MICP is applied for field applications including biostimulation and bioaugmentation. Although bioaugmentation strategy using efficient ureolytic biocementing culture of Sporosarcina pasteurii is widely practiced, the impact of native ureolytic microbial communities (NUMC) on CaCO3 mineralisation via S. pasteurii has not been explored. In this paper, we investigated the effect of different concentrations of NUMC on MICP kinetics and biomineral properties in the presence and absence of S. pasteurii. Kinetic analysis showed that the biocementation potential of S. pasteurii is sixfold higher than NUMC and is not significantly impacted even when the concentration of the NUMC is eight times higher. Micrographic results revealed a quick rate of CaCO3 precipitation by S. pasteurii leading to generation of smaller CaCO3 crystals (5–40 µm), while slow rate of CaCO3 precipitation by NUMC led to creation of larger CaCO3 crystals (35–100 µm). Mineralogical results showed the predominance of calcite phase in both sets. The outcome of current study is crucial for tailor-made applications of MICP.